Morphology of the endothelium over atherosclerotic plaques in human coronary arteries. Issue 6 (December 1988) - Davies, M J; Woolf, N; Rowles, P M; Pepper, J
Abstract : The right coronary arteries of six hearts removed from patients with atherosclerosis, who were undergoing cardiac transplantation, were perfused with 2% buffered glutaraldehyde for 20 minutes before preparation for scanning electron microscopy. Perfusion was started within five minutes of explanation. In two patients the artery was angiographically normal, in one it was irregular in outline, and three had focal segments with significant stenosis. None of the patients had concentrations of plasma lipids above 5.5 mmol/l. The endothelial surface showed widespread focal abnormalities ranging from adhesion and migration of monocytes to loss of individual endothelial cells. Larger areas of endothelial denudation with exposure of underlying collagen were also seen consistently. Loss of endothelial cells was associated with accumulation of monocytes, on and deep to the surface, as well as adhesion of platelets to the exposed subendothelial tissue. These results accord with the endothelial damage and platelet adhesion seen in hyperlipidaemic animals fed a high lipid diet.